Generalization of FuzzyContra- Continuous Functions in Fuzzy Topological Space - Mohisn, Salim dawood (Al-Qadisiyah Journal of Pure Science, 2017)
in this paper, we devoted the generalization of some types of fuzzy contra-continuous functionsnamely fuzzy contra-g-continuous with study and discussion some properties of these types, also we shows relationships between these types. Keywords:- ((fuzzy g-closed set, fuzzy contra-g- continuous function, fuzzy 2 1 T -space, fuzzy gcompact space, fuzzy continuous function))